FEATURES OF REGULATION OF NON-BANK FINANCIAL INSTITUTIONS OF UKRAINE - Sulyma, Maryana; Nesvidoma, Maryna (Socio-economic relations in the digital society, 2020)
The article considers the problems of state regulation of the financial services market. The regulation of each market sector will differ depending on whether the financial institution attracts customer funds. Thus, banks, insurance companies and credit unions operate with funds raised from customers, while other financial institutions operate on the basis of equity. The key task of the regulator is to make supervision of the activities of these organizations adequate to the risks inherent in the activities of each of them. At the same time, companies that operate on the basis of equity should not feel the excessive presence of the regulator in their activities. In this paper the normative-legal provision of state regulation of non-banking financial institutions is analyzed. Considerable attention is paid to the study of new requirements for the regulation of non-bank financial institutions. After all, on July 1, 2020, the Law of Ukraine «On Financial Services and State Regulation of Financial Services Markets» was adopted, which provides for the liquidation of the National Commission for Regulation of Financial Services Markets and distribution of financial market regulation powers between two regulators, namely the National Bank of Ukraine and the National Commission on Securities and Stock Market. In addition, considerable attention is paid to the model of regulation and supervision of financial institutions, as well as the supervision of banks, which is carried out in a risk-oriented approach. The new regulation and supervision in the non-banking financial sector will be implemented according to international standards in the same way as in the banking sector. The main task of the regulator is to make the supervision of the activities of these organizations adequate to the risks inherent in the activities of each of them. At the same time, companies that operate on the basis of equity should not feel the excessive presence of the regulator in their activities. In addition, the article examines the new requirements of the Law «On Prevention and Counteraction to Legalization (Laundering) of Proceeds from Crime, Financing of Terrorism and Financing of Proliferation of Weapons of Mass Destruction», which was approved on 16.08.2020 and aimed at protecting the rights and legitimate interests of citizens, society and the state, as well as ensuring national security. The activity of non-bank financial institutions is analyzed and the impact of the Covid-19 crisis on their activity is determined.
Keywords: banks; non-bank financial institutions; law; «split»; regulator; crisis; financial services market